10.1001/TESTjama.2012.4607 (CrossRef Listing of Deleted DOIs, 2000)
IMPORTANCE: Modulating perioperative inflammation could be associated with fewer postoperative complications and better outcomes in major digestive surgery. The clinical benefit of corticosteroids with this purpose remains controversial. OBJECTIVE: To assess whether preoperative high-dose corticosteroids improve postoperative outcomes after surgery for digestive cancer. DESIGN, SETTING, AND PARTICIPANTS: This double-blind, placebo-controlled, superiority randomized clinical trial included patients undergoing elective surgery with curative intent for digestive cancer. This was a multicenter trial with the participation of 23 French hospitals working as a reference for digestive surgical oncology. Among patients referred for major digestive surgery to the participating centers, those undergoing surgery for digestive cancer with a curative intent between 2019 and 2023 were randomized. Patients undergoing only hepatic surgery without digestive anastomosis were excluded. INTERVENTIONS: Patients included were randomized to receive either 20 mg/kg of intravenous methylprednisolone at the time of anesthesia or a placebo with an identical aspect. MAIN OUTCOMES AND MEASURES: The primary end point was the onset of major postoperative complications within 30 days after surgery. Secondary end points were postoperative infections, intra-abdominal infections, wound infections, unsatisfactory wound healing within 30 days after surgery, and the length of hospital stay after surgery. RESULTS: Among 2461 patients referred for major digestive surgery, 1210 patients (mean [SD] age, 65.9 [11.3] years; 762 male [63%]) undergoing surgery for digestive cancer were randomized. Among the 1188 patients with follow-up at postoperative day 30 (594 per arm), major postoperative complications did not significantly differ between the 2 groups (139 of 594 [23%] receiving methylprednisolone vs 119 of 594 [20%] receiving placebo; P = .16). Secondary outcomes did not differ either between the group receiving methylprednisolone and the group receiving placebo (postoperative infections: 182 of 594 [31%] vs 177 of 594 [30%]; P = .75; intra-abdominal infections: 142 of 594 [24%] vs 126 of 594 [21%]; P = .27; unsatisfactory wound healing: 87 of 594 [15%] vs 69 of 594 [12%]; P = .13; mean [SD] length of hospital stay: 13.21 [8.59] days vs 12.97 [8.1] days; P = .93). CONCLUSIONS AND RELEVANCE: A preoperative pulse dose of corticosteroids had no benefit on postoperative outcomes in elective digestive cancer surgery and should not be recommended in routine practice. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT03875690.